The Effectiveness of Digital Comics in Improving Science Learning Outcomes and Scientific Attitudes of Fourth-Grade Elementary Students - Tristaningrat, Adi Nugraha; Ariyana, I Komang Sesara (Universitas Pendidikan Ganesha, 2025)
The lack of innovative and contextual media in science instruction at the elementary level contributes to low student learning outcomes and scientific attitudes. This study aimed to analyze the effectiveness of interactive digital comic media on learning outcomes and scientific attitudes in science learning among fourth-grade elementary students. A quasi-experimental design was employed with control and experimental groups. The sample consisted of 55 students divided into two groups: the experimental group used digital comic media, while the control group used conventional teaching materials. Instruments included a science achievement test and a scientific attitude questionnaire. Data were analyzed using an independent samples t-test. The results showed that the use of digital comics significantly improved student learning outcomes (t = 5.216; p < 0.05) and scientific attitudes (t = 4.881; p < 0.05). The study concludes that interactive digital comic media is effective in enhancing conceptual understanding and fostering scientific attitudes among students. Its implication is that teachers can adopt digital comics as an engaging and contextually relevant instructional alternative in elementary science education.